Treinamento de aplicadores via vídeo modelação para implementação de ensino por tentativas discretas - Santini, Giovanna Jangarelli (2024)
Discrete trial teaching is one of the 28 evidence-based practices for autism. However, Applied Behavior Analysis-based interventions come with a high implementation cost for families, making this practice difficult to access. Therefore, it seems pertinent to investigate the effects of an instructional program using video modeling on the behavior of implementers for the implementation of discrete trial teaching, aiming for greater dissemination of evidence-based practices for interventions with this population. The study involved three individuals aged 18 years or older who had no prior exposure to this teaching model and were newly hired at a private clinic where the research was conducted. The research utilized a multiple probe experimental design and resulted in significant improvement among all participants in protocol implementation when comparing baseline data with probe data.